2015
DOI: 10.1002/cncr.29210
|View full text |Cite
|
Sign up to set email alerts
|

Trends in imaging after diagnosis of thyroid cancer

Abstract: Background The largest growth in differentiated thyroid cancer (DTC) diagnosis is in low-risk cancers. Trends in imaging after DTC diagnosis are understudied. Hypothesizing a reduction in imaging utilization due to rising low-risk disease, we evaluated post-diagnosis imaging patterns over time and patient characteristics that are associated with likelihood of imaging. Methods Using the Surveillance Epidemiology and End Results-Medicare database, we identified patients diagnosed with localized, regional or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Unnecessary diagnosis and intervention of low-risk and clinically non-significant disease remain a legitimate concern [34]. However, it is important to note that the imaging results analyzed in this study influenced patient management in over 50 % of patients, of whom 17 (37 %) were operated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unnecessary diagnosis and intervention of low-risk and clinically non-significant disease remain a legitimate concern [34]. However, it is important to note that the imaging results analyzed in this study influenced patient management in over 50 % of patients, of whom 17 (37 %) were operated.…”
Section: Discussionmentioning
confidence: 98%
“…The rise in use of diagnostic imaging, especially of FDG-PET(/CT) in TC follow-up, leads to increased radiation exposure and associated health costs [3234]. Unnecessary diagnosis and intervention of low-risk and clinically non-significant disease remain a legitimate concern [34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Surveillance, Epidemiology, and End Results Medicare database study demonstrated a trend toward increased use of postdiagnostic imaging modalities across all risk categories over recent decades. 13 Although thyroid cancer is a disease with a relatively low clinical recurrence and death burden, the economic burden of the disease is not insignificant and continues to grow. A review of surveillance practices to improve cost-effectiveness in low-risk PTC could significantly curb the rising costs of thyroid cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…Directly ionizing gamma-radiation from radioisotopes such as 99m Tc can also provide real-time information during minimally invasive surgeries using a portable detector such as Geiger–Müller devices [ 18 ]. Furthermore, both beta and gamma-ray irradiation radionuclides like 131 I can be simultaneously applied for radiotherapy by beta-ray irradiation and for conducting imaging diagnosis using the beta or gamma-ray by SPECT, gamma camera, or PET [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%